Alternatives to the efficient market hypothesis: An overview - Kingstone Nyakurukwa; Yudhvir Seetharam (Journal of Capital Markets Studies (JCMS), 2023)
Purpose - The authors' goal is to provide an overview and historical context for the various alternatives to the efficient market hypothesis (EMH) that have emerged over time. The authors found eight current alternatives that have emerged to address the EMH's flaws. Each of the proposed alternatives improves some of the assumptions made by the EMH, such as investor homogeneity, the immediate incorporation of information into asset values and the inadequacy of rationality to explain asset prices. Design/methodology/approach - To come up with the list of studies relevant to this review article, the authors used three databases, namely Scopus, Web of Science and Google Scholar. The first two were mostly used to get peer-reviewed articles while Google Scholar was used to extract articles that are still work in progress. The following words were used as the search queries; "efficient market hypothesis" and "alternatives to the efficient market hypothesis". Findings - The alternatives to the EMH presented in this article demonstrate that market efficiency is a dynamic concept that can be best understood with a multidisciplinary approach. To better comprehend how financial markets work, it is crucial to draw on concepts, theories and ideas from a variety of disciplines, including physics, economics, anthropology, sociology and others. Originality/value - The authors comprehensively summarise the current state of the behavioural finance literature on alternatives to the EMH.
Keywords: 330; Asset pricing; Behavioural finance; Econophysics; Efficient market hypothesis